2006
DOI: 10.1007/s00466-006-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microelectromechanical Systems (MEMS) Devices by the Meshless Point Weighted Least-squares Method

Abstract: In this paper, the characteristics of microelectromechanical systems (MEMS) devices are analyzed by a meshless method-point weighted least-squares (PWLS) method. In the present meshless method, field nodes and collocation points are adopted. The field nodes are used to construct the trial functions based on locally supported interpolation domains. The collocation points that can be independent of the field nodes are adopted to evaluate the total residuals of the problem domain and its boundaries. The least-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…However, for higher voltage, i.e.Ṽ = 13.8, 14.2 and 15 V, solutions become unstable at 0.92, 1.13 and 1.68 ms, respectively. All these results are in very close agreement with the results reported by Wang et al [45].…”
Section: Example 2 (A Fixed-fixed Microswitch Wang Et Al [45])supporting
confidence: 95%
See 1 more Smart Citation
“…However, for higher voltage, i.e.Ṽ = 13.8, 14.2 and 15 V, solutions become unstable at 0.92, 1.13 and 1.68 ms, respectively. All these results are in very close agreement with the results reported by Wang et al [45].…”
Section: Example 2 (A Fixed-fixed Microswitch Wang Et Al [45])supporting
confidence: 95%
“…This microswitch may be modeled as a Timoshenko beam. The governing equations may be written as follows [45]:…”
Section: Example 2 (A Fixed-fixed Microswitch Wang Et Al [45])mentioning
confidence: 99%
“…Kuang and Chen (2005) employed the Adomian decomposition method (ADM) to analyze the nonlinear pull-in behavior in electrostatic micro-actuators and showed that the ADM technique enabled the derivation of highly precise analytical solutions without the need for any simplifying assumptions regarding the nonlinear system. Wang et al (2007) analyzed MEMS devices using a meshless point weighted least-squares (PWLS) method and showed that the results were comparable with those obtained by other simulation approaches and experimental data.…”
Section: Introductionsupporting
confidence: 79%
“…For wide prismatic microbeams, several researchers have incorporated Palmer's model (Palmer 1937) to account for the effect of fringing field capacitance (Osterberg and Senturia 1997;Pamidighantam et al 2002;Wang et al 2007). For narrow and thick microbeams, Batra et al (2006) demonstrated the effectiveness of an improved fringing model obtained by using the Method of Moments (MoM).…”
Section: Verification Of the Fringing Field Model And The Displacemenmentioning
confidence: 98%
“…For a prismatic beam having constant widthb, the expression for distributed electrostatic force using the Palmer's model of fringing field capacitance (Palmer 1937) is written as (Osterberg and Senturia 1997;Pamidighantam et al 2002;Batra et al 2006;Wang et al 2007)…”
Section: Introductionmentioning
confidence: 99%